Finding clarity in the fog of hybrid warfare - Li, Ian (2025)
Singapore’s interest in hybrid warfare grew significantly following the Russian annexation of Crimea in 2014. Although the term has gained mainstream attention, there remains much ambiguity over its meaning. Several defining attributes in hybrid warfare can help shape response measures.